Dyeing of Silk Fabric with Natural Wall Nut Tree Wood Dye and Its Ultraviolet Protection Properties. Issue 15 (23rd November 2022) - Wang, Shiwen; Wang, Linan; Wu, Minghua; Song, Kaili; Yu, Zhicheng
ABSTRACT: Maintaining color fastness and endow functionality of the fabrics dyed with natural colorants had been the major constraint of natural dye in modern textile practices. In this work, a natural dye was extracted from wall nut tree wood. The dye solution extracted from wall nut tree wood showed excellent thermal stability until 100°C. The structure and functional groups of the extracted dye were investigated by FTIR. The optimum dyeing process was performed at a pH about 4.5 at 90°C for 60 min. In this experiment, three different mordants were used to make silk fabrics show different colors and can improve the color fastness of wall nut tree wood. Finally, the color fastness of wall nut tree wood dye can be further improved by using a dye-fixing agent, and solve the problem of poor color fastness of natural dyes. The dye-fixing agent formed a protective film on the surface of the dyed silk fabrics. The protective film reduced the water solubility of the wall nut tree wood dye, thereby improving the color fastness of the dyed silk fabrics. The best washing fastness reached grade 3–4, and the sunlight fastness reached grade 4. The natural wall nut tree wood dye also showed excellent UV protection properties, and the UPF value of the dyed fabric was 50 + . The wall nut tree wood was expected to become a functional natural dye in the future.